ICN‐Oriented secure propagation for smart ideology and politics. Issue 5 (2nd February 2022) - Gao, Miao
Abstract : Besides the in‐network caching, Information‐Centric Networking (ICN) has also an obvious feature, that is, security distribution which could guarantee that all contents are retrieved correctly. As we know, Smart Ideology and Politics (SIP) has gained great attention from some research centers so as to ensure the national security, this is because there are many unreliable propagations on SIP. In order to realize the secure propagation for SIP, the security distribution feature of ICN could be exploited. Therefore, this letter proposes ICN‐oriented Secure Propagation for SIP, called ISP4S, including two major parts. At first, ICN network paradigm is employed to build a bran‐new infrastructures. Then, for SIP, the differential privacy protection method is proposed to construct the corresponding secure propagation paths. For the proposed ISP4S, some simulations based on ICN environment are made to verify its efficiency, and the experimental results demonstrate that ISP4S outperforms the selected baselines. Abstract : ICN‐based content security mechanism framework relies on ICN paradigm, including two main roles, that is, SIP publisher (producer) and SIP subscriber (consumer). SIP is propagated via the ICN‐oriented environment. SIP publisher tries to provide the secure SIP at least it guarantees that the content itself is secure. SIP subscriber is to obtain the secure SIP from the ICN‐oriented environment.